A Model for Full-Fledged Inflation Targeting and Application to Ghana - Clinton, Kevin (IMF Working Papers; Working Paper ;, 2010)
A model in which monetary policy pursues full-fledged inflation targeting adapts well to Ghana. Model features include: endogenous policy credibility; non-linearities in the inflation process; and a policy loss function that aims to minimize the variability of output and the interest rate, as well as deviations of inflation from the long-term low-inflation target. The optimal approach from initial high inflation to the ultimate target is gradual; and transitional inflation-reduction objectives are flexible. Over time, as policy earns credibility, expectations of inflation converge towards the long-run target, the output-inflation variability tradeoff improves, and optimal policy responses to shocks moderate.